Implementation of diferrentiated instruction in improving students’ learning outcomes in aqidah akhlaq at Tarbiyah Mazniyah Islamic Junior high school, Jambi city - Duta Anggoro; Hindun (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study is motivated by the low learning outcomes of students in the Aqidah Akhlak subject, which are associated with limited variation in teaching methods, low student engagement, lack of concentration, passive participation, and decreased motivation to learn. These conditions indicate the need for a more adaptive and student-centered learning approach. Therefore, this study aims to analyze the implementation of differentiated instruction in improving students’ learning outcomes in Aqidah Akhlak learning. This research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, which consists of four stages: planning, acting, observing, and reflecting, conducted in two cycles with 33 Grade VIII students at Madrasah Tsanawiyah Tarbiyah Mazniyah Jambi. Data were collected through observation, interviews, and tests, and analyzed using descriptive quantitative and qualitative techniques. The results showed a significant improvement in students’ learning outcomes, as indicated by the increase in mastery levels from 55% (18 students) in the pre-cycle to 67% (22 students) in Cycle I, and reaching 100% (33 students) in Cycle II. In addition, student engagement and participation improved during the learning process. These findings indicate that differentiated instruction is effective in improving both learning outcomes and student engagement, and is relevant to be implemented in Aqidah Akhlak learning within the framework of student-centered education